Besieged City of time: Control and negotiation of generation Z youth in platform swinging - Yang, Mengge (Universitas Ahmad Dahlan, 2024)
The rapid development of information technology and the proliferation of digital media have made social media platforms an integral part of Generation Z's daily lives. In this context, the “distributive use” behavior of social media has emerged or what is referred to as platform swinging, which is the habit of constantly switching between platforms. This behavior causes constant distraction and keeps many young Generation Z individuals stuck in a “time warp”. In this context, the “distributive use” behavior of social media has emerged or what is referred to as platform swinging, which is the habit of constantly switching between platforms. This behavior causes constant distraction and leaves many young Generation Z individuals stuck in a “time warp”. This research aims to understand the characteristics and logic behind Generation Z's platform swinging behavior and its impact on their time management. Using a qualitative approach, this research utilizes in-depth interviews and virtual ethnography to capture the patterns of media interaction that occur in the real world. The results show that platform swinging behavior is driven by various factors, such as the need for social connectedness, boredom, and platform algorithms that encourage constant interaction. However, this behavior also has negative impacts, such as decreased productivity, stress, and poor time management. The discussion leads to the importance of awareness of wise media use and strategies to manage platform swinging so as not to disrupt life balance. It is hoped that this research can help Generation Z find ways to control and negotiate their use of social media so that they can escape the “siege of time” and achieve a better balance in their daily lives.